2022
DOI: 10.1039/d2fo00697a
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the impact of viscosity and starch type on the in vitro starch digestibility of different gels

Abstract: Starch is one of the most important carbohydrate that is present in many foods. Gelatinization is an important property of starch, associated with physical changes that promotes an increase in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In vitro digestibility was analyzed following the method previously described with minor modifications [ 18 ]. The amount of gel for each sample was weighed to maintain a constant enzyme/starch ratio of 14 U/mg starch.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro digestibility was analyzed following the method previously described with minor modifications [ 18 ]. The amount of gel for each sample was weighed to maintain a constant enzyme/starch ratio of 14 U/mg starch.…”
Section: Methodsmentioning
confidence: 99%
“…The rheological experiments to determine the starch digestion were carried out using a starch pasting cell (ST24-2D/2V/2V-30) as described previously [ 18 ] with some modifications. A solvent trap kit was used to minimize water evaporation.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it was found that the G was higher than G over the entire frequency range studied, indicating that all water caltrop starch pastes were considered as elastic solids rheologically. When deformation increased, the network structure of water caltrop starch pastes gradually collapsed, leading to significant slope change in G over the frequency range studied to weak gel structure [47]. However, under a total tempering time of 96 h, cycle numbers of cycled ANN showed less impact on the dynamic shear rheological properties.…”
Section: Dynamic Rheological Propertiesmentioning
confidence: 97%
“…As expected, the apparent viscosity plots for corn, wheat, and rice indicate differences in their pasting performance, with corn showing an earlier swelling and major maximum apparent viscosity (2866 ± 15 mPa s) than observed in the other starches, which agree with previously reported results. [4] Moreover, Wickramasinghe et al [15] observed different viscosity peaks and swelling power among several varieties of hard or soft wheat starches. Rice showed lower apparent peak viscosity (2263 ± 93 mPa s), with similar value to the one reported.…”
Section: Viscosity Hydrolysismentioning
confidence: 99%
“…[2,3] Particularly in the case of starch digestion, the oro-gastrointestinal digestion is rather challenging due to the many dilutions that masked the kinetic changes in the starch fraction. [4] Alternatively, in vitro starch digestion methods are the most applied ones, DOI: 10.1002/star.202200189 mainly based on enzymatic hydrolysis followed by measuring the glucose release. [5] However, other indirect methods for assessing starch performance along enzymatic digestion have also attracted attention, particularly following viscosity [6] and the impact of different enzyme concentrations [7] during digestion simulation, initially using a rotary viscometer.…”
Section: Introductionmentioning
confidence: 99%